Evaluation of Three Hydration Strategies in Detection Dogs Working in a Hot Environment - Otto, Cynthia M.; Hare, Elizabeth; Nord, Jess L.; Palermo, Shannon M.; Kelsey, Kathleen M.; Darling, Tracy A.; Schmidt, Kasey; Coleman, Destiny (Frontiers in Veterinary Science, 2017)
Physical activity in hot environments can increase the risk of heat stress or heat stroke in dogs. Heat tolerance is influenced by acclimatization to the environment, physical fitness, and hydration state. Three common strategies to promote hydration in working dogs are free access to water (W), oral electrolyte solutions (OESs), and administration of subcutaneous fluids (SQs). None of these methods have been compared for safety or efficacy in a working environment. In a cross-over design, seven vehicle-screening canines were randomly assigned to each of the three hydration strategies during working shifts at the Sarita, TX checkpoint. Physical, behavioral, and biochemical parameters were collected before, during, and after a work shift (mean 5.7 ± 0.8 h). Dogs were given 10 mL/kg oral W, 10 mL/kg chicken flavored OES, or 15 mL/kg of SQs initially followed by controlled access to W or OES. The dogs drank 15.61 ± 4.47 mL/kg/h of W and OES when in the OES group, compared to 7.04 ± 3.42 and 5.56 ± 4.40 mL of W, for the W and SQ groups, respectively. The median environmental temperature was 84.8°F (29.3°C). The median humidity was 70%. Based on mixed effects linear modeling, dogs in the OES and SQ groups had significantly higher total CO2, and lower packed cell volume and total plasma protein at the end of the day. Creatinine increased a small but significant amount in the SQ group and decreased in the OES group. Searching behaviors were independent of hydration strategy but highly related to the dog specific factors of sex, breed, and activity level. Under conditions of controlled activity in moderate heat and humidity, dogs accustomed to the work and the environment were more likely to increase fluid consumption and hydration when provided a flavored OES. Potential benefits of OES and SQ were indirect and no adverse effects were documented for any of the hydration strategies tested.